2010
DOI: 10.4049/jimmunol.0901889
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Injury Enhances Dendritic Cell Immunogenicity via TLR4 and NF-κB Activation

Abstract: Ischemic (isc) injury during the course of transplantation enhances the immunogenicity of allografts and thus results in poorer graft outcome. Given the central role of dendritic cells (DCs) in mounting alloimmune responses, activation of donor DCs by ischemia may have a primary function in the increased immunogenicity of isc allografts. In this study, we sought to investigate the effect of ischemia on DC activity in vitro. Following induction of ischemia, bone marrow-derived DCs were shown to augment allogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 86 publications
(117 reference statements)
0
40
0
Order By: Relevance
“…The autoreactive T-cell assay was performed as above using NOR MSCs in an ELISPOT assay as previously described (16). ELISPOT kits (BD Biosciences) to assess IFN-γ and IL-6 production were used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The autoreactive T-cell assay was performed as above using NOR MSCs in an ELISPOT assay as previously described (16). ELISPOT kits (BD Biosciences) to assess IFN-γ and IL-6 production were used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…To assess cytokine production of murine serum and culture supernatant samples, a 21-plex cytokine kit (Millipore, St. Charles, MO) was used according to the manufacturer's instructions and as previously described (16). To assess production of IFN-α, M-CSF, and Flt3L, murine ELISA kits (R&D Systems, Minneapolis, MN) were used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Proinflammatory cytokine expression by DCs is an important indicator of DC activity 23,24 and our data for mRNA expressions of these cytokines on BMDC after coculture are provided in Supplemental Figure S1 (see Supplementary Material and Supplementary Fig. S1, http://www.iovs.org/ lookup/suppl/doi:10.1167/iovs.12-9547/-/DCSupplemental).…”
Section: Ded Induces Corneal Expression Of Endogenous Tlr4 Ligandsmentioning
confidence: 99%
“…In a more recent study on an in vitro -induced ischemia model, bone marrow–derived DCs were shown to augment allogeneic T-cell proliferation as well as the interferon-gamma response (Jurewicz et al, 2010). In this study, TLR4 ligation was also shown to occur in ischemic DCs, most likely – as concluded by the authors – in response to HSP70, which was found to be elevated in DCs after ischemic injury.…”
Section: Role Of Heat Shock Protein 70 In Innate Alloimmunitymentioning
confidence: 99%